Living wills in the nursing profession: knowledge and barriers - Losa Iglesias, Marta Elena; Becerro de Bengoa Vallejo, Ricardo (Acta Bioethica, 2013)
The aims of this study were to understand Spanish nurses’ knowledge about living wills and legal regulations and to explore their experiences, needs and challenges in these situations using quantitative and qualitative approaches. The first part of the study was a descriptive survey administered to a convenience sample of nurses (454 individuals) who worked in hospitals and other primary care clinics in the Principality of Asturias in northern Spain. The survey tested their knowledge of living wills and related major legal issues. At the end of the survey, the nurses were asked to provide a personal email address if they were interested in participating in a personal interview. In the second part of this study, we used a qualitative phenomenological approach based on Husserl’s framework. The results indicate that nurses are not sufficiently knowledgeable about the use of LWD in clinical practise. As a consequence, they are unable to support patient autonomy in health care treatment decisions.